The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.tet.2015.05.093
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of dihydrolysergic acid and dihydrolysergol: development of a divergent synthetic strategy applicable to rapid assembly of D-ring analogs

Abstract: The total syntheses of dihydrolysergic acid and dihydrolysergol are detailed based on a Pd(0)-catalyzed intramolecular Larock indole cyclization for the preparation of the embedded tricyclic indole (ABC ring system) and a subsequent powerful inverse electron demand Diels–Alder reaction of 5-carbomethoxy-1,2,3-triazine with a ketone-derived enamine for the introduction of a functionalized pyridine, serving as the precursor for a remarkably diastereoselective reduction to the N-methylpiperidine D-ring. By design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 87 publications
1
28
0
Order By: Relevance
“…12 The exploration and development of the 1,2,3-triazine cycloaddition reactions was inspired by their projected use in the total syntheses of natural products that now include dihydrolysergic acid, 13 pyrimidoblamic acid, 14 P-3A, 14 and methoxatin. 15 …”
mentioning
confidence: 99%
“…12 The exploration and development of the 1,2,3-triazine cycloaddition reactions was inspired by their projected use in the total syntheses of natural products that now include dihydrolysergic acid, 13 pyrimidoblamic acid, 14 P-3A, 14 and methoxatin. 15 …”
mentioning
confidence: 99%
“…11 Recently, our efforts extended to 1,2,3-triazines, examining the synthesis and cycloaddition reaction scope of the parent 1,2,3-triazine and a series of 1,2,3-triazines that contain electron-withdrawing groups at sites where their electronic impact was both consonant and dissonant to that innate to the 1,2,3-triazine core (Figure 1). 12 In addition to defining the scope of the 1,2,3-triazine cycloaddition reactions, these studies have also found application in the total syntheses of (−)-pyrimidoblamic acid and P-3A 13 as well as the late-stage divergent total syntheses of dihydrolysergic acid, dihydrolysergol, and a series of heterocyclic derivatives 14 .…”
mentioning
confidence: 99%
“…There are no direct precedents for the structure of (I) in the crystallographic literature (CSD version 5.39, update of August 2018;Groom et al, 2016). However, there are several precedents for (E)-N-benzylidene-5,6,7,8-tetrahydronaphthalen-1-amine and (E)-N-[(2-ethoxynaphthalen-1-yl)methylene]aniline including 2-(4-isopropylphenyl)-1,3-diphenyl-2,3dihydro-1H-naphtho[1,2-e][1,3]oxazine (Borah et al, 2014), 2-(2-nitrophenyl)-3-(5,6,7,8-tetrahydronaphthalen-1-yl)-1,3thiazolidin-4-one (Drawanz et al, 2017) (Wu et al, 2013) and methyl (5aR,6aR,9R,-10aR)-4-benzoyl- 7-methyl4,5,5a,6,6a,7,8,9,10,10adecahydroindolo[4,3-fg]quinoline-9-carboxylate dihydrate (Lee et al, 2015).…”
Section: Database Surveymentioning
confidence: 99%